East of Eden Premiere Party - unknown:::Creator:::::::::::: (USA)
At the premiere party for East of Eden. From left to right: back: John Steinbeck, Elaine Steinbeck, Jack Warner, an unidentified man. Front: Elia Kazan and Molly Kazan. See also 1-549.